Diabetes and HIV - Salam, Ranabir; Bajaj, Sarita; Kapoor, Nitin; Saboo, Banshi; Dasgupta, Arundhati (Journal of Social Health and Diabetes, 2019)
In India, the prevalence of HIV infection among adults (15–49 years) is estimated at 0.26%. The total number of people living with HIV (PLHIV) in India was estimated at 21.17 lakhs in 2015. There has been a declining trend in the mortality rate of HIV-infected patients on antiretroviral therapy (ART). With HIV becoming a chronic manageable disease, metabolic complications like diabetes mellitus (DM) and dyslipidemia are coming to the forefront. Generally, protease inhibitors (PI) are implicated in metabolic derangement; however, nucleoside reverse transcriptase inhibitors (NRTI) like stavudine can also cause diabetes. Among HIV-infected patients, the prevalence of diabetes is reported to range from 2 to 19%, so there is strong case for screening of diabetes among HIV-infected cases. The South Asian Consensus Guidelines recommend that both fasting and postprandial glucose values should be checked at screening and during monitoring of therapy. National AIDS Control Organization (NACO) recommends fasting plasma glucose with value ≥ 126 mg% diagnostic of diabetes mellitus. HbA1c may underestimate the degree of hyperglycemia in HIV-infected individuals and may not be a good diagnostic tool. Lifestyle modification is recommended as part of treatment. Metformin should be used with caution in HIV patients. Concomitant use of metformin with non-nucleoside reverse transcriptase inhibitors (NNRTI) can cause lactic acidosis. Thiazolidinediones should be the drug of choice in HIV, particularly in patients with lipodystrophy. Insulin secretagogues (meglitinides and sulfonylureas) are safe but may not be effective in the presence of severe insulin resistance. There are concerns regarding the use of gliptins in HIV-infected patients as they have molecular targets on immune cells. Insulin should be the drug of choice for HIV-infected patients with marked hyperglycemia (HbA1c > 9%), ketonuria, severe liver disease, or severe kidney disease. SGLT2 inhibitor may increase the risk of urinary tract infection and genital mycotic infections in HIV-infected diabetics. Regarding the use of ART among HIV patients with diabetes, NACO guidelines recommend that Tenofovir, lamivudine, and efavirenz should be used as first-line ART for all new patients, except known cases of severe diabetes, severe hypertension, or renal disease. Tenofovir, lamivudine, and lopinavir/ritonavir should be used as first line in women ever exposed to single dose Nevirapine in the past and also for all confirmed HIV-2 or HIV-1 & 2 coinfected patients. HIV infected with diabetes mellitus and microalbuminuria or proteinuria need Abacavir-based regimen (Abacavir + Lamivudine + Efavirenz). There is some suggestion that PI-based regimes should be avoided in patients at high risk of developing diabetes, for example, those with a history of gestational diabetes, positive family history of diabetes, or impaired glucose tolerance on screening.
Keywords: PLHIV and diabetes; ART and metabolic derangement; management of HIV dysglycemia